2019
DOI: 10.3390/educsci9010058
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Engineering Student Learning Style Trends by Using Multivariate Statistical Analysis

Abstract: This study aims to use group technology to classify students at the classroom level into clusters according to their learning style preferences. Group technology is used, due to the realization that many problems are similar, and that by grouping similar problems, single solutions can be found for a set of problems. The Felder and Silverman style, and the index learning style (ILS) are used to find student learning style preferences; students are grouped into clusters based on the similarities of their prefere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 24 publications
(28 reference statements)
0
9
0
1
Order By: Relevance
“…This questionnaire lists the Course Learning Outcomes (CLOs) that the students have to utilize to assess their predefined CLOs. 15 Online learning overlaps with the concept of distance learning, which uses earlier technologies such as educational television and videoconferencing. Previous studies of distance learning concluded that these technologies were not significantly different from regular classroom learning in effectiveness.…”
Section: Significance For Public Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…This questionnaire lists the Course Learning Outcomes (CLOs) that the students have to utilize to assess their predefined CLOs. 15 Online learning overlaps with the concept of distance learning, which uses earlier technologies such as educational television and videoconferencing. Previous studies of distance learning concluded that these technologies were not significantly different from regular classroom learning in effectiveness.…”
Section: Significance For Public Healthmentioning
confidence: 99%
“…This questionnaire lists the Course Learning Outcomes (CLOs) that the students have to utilize to assess their predefined CLOs. 15 …”
Section: Introductionmentioning
confidence: 99%
“…FSLSM has been used to date in several studies involving learner behavior modeling in LMS such as Aissaoui et al. (2018) , Abdelhadi et al. (2019) , and Ferreira et al.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, most of the research, which explored the effect of cognitive styles on individual performance, was focused on human resource implications within organizations, such as team performance, productivity, adaptability, and entrepreneurial attitude, to mention a few [12][13][14]. Cognitive style studies in engineering education are scarce and seem to focus on the student's cognitive level [15], cognitive operations [16], personality traits and mental skills [17], and learning styles [18]. Less at-tention was given to the role of a student's cognitive styles in their academic performance, especially in engineering education.…”
Section: Introductionmentioning
confidence: 99%